Imaging in the Diagnosis and Management of Necrotizing Otitis Externa: A Survey of Practice Patterns. Issue 5 (June 2018) - Cooper, Timothy; Hildrew, Douglas; McAfee, Jacob S.; McCall, Andrew A.; Branstetter, Barton F.; Hirsch, Barry E.
Abstract : Objective: To survey neurotologists and head and neck radiologists regarding use of imaging in the diagnosis and management of necrotizing otitis externa (NOE). Study Design: Cross-sectional survey study. Setting: Online survey distributed through email to specialty society membership lists. Participants: Neurotologists and head and neck radiologists with membership in either the American Neurotology Society or The American Society of Head and Neck Radiology. Main Outcome Measures: Responses to survey consisting of two demographic and seven clinically oriented questions related to the use of imaging in the diagnosis and management of NOE. Results: One hundred thirty-six participants responded to the survey. The imaging modality of choice in establishing the diagnosis of NOE selected by the respondents was computed tomography (CT) (37.5%) followed by technetium scintigraphy (21.3%). Magnetic resonance imaging (MRI) was the preferred investigation by 41.9% of participants for determining extent of disease. Gallium scanning was the imaging modality preferred by 32.4% of respondents for determining when to cease medical therapy. Ninety-five percent of participants responded that CT scans were always or frequently used in the diagnosis and management of NOE compared with 72.8% for MRI, 34.5% for gallium scans, and 34.2% for technetium scans. Conclusions: There is considerable heterogeneity in the preferred imaging modalities used in the diagnosis and management of NOE. CT and MRI are the preferred contemporary modalities used by many physicians, demonstrating a shift away from the historic use of nuclear medicine scans. Abstract : Supplemental Digital Content is available in the text